Refined chelator spacer moieties ameliorate the pharmacokinetics of PSMA-617 - Santos, José Carlos dos; Schäfer, Martin; Bauder-Wüst, Ulrike; Beijer, Barbro; Eder, Matthias; Leotta, Karin; Kleist, Christian; Meyer, Jan-Philip; Dilling, Thomas R.; Lewis, Jason S.; Kratochwil, Clemens; Kopka, Klaus; et al. (Frontiers in Chemistry, 2022)
Prostate-specific membrane antigen (PSMA) binding tracers are promising agents for the targeting of prostate tumors. To further optimize the clinically established radiopharmaceutical PSMA-617, novel PSMA ligands for prostate cancer endoradiotherapy were developed. A series of PSMA binding tracers that comprise a benzyl group at the chelator moiety was obtained by solid-phase synthesis. The compounds were labeled with 68Ga or 177Lu. Competitive cell-binding assays and internalization assays were performed using the cell line C4-2, a subline of the PSMA positive cell line LNCaP (human lymph node carcinoma of the prostate). PET-imaging and biodistribution studies were conducted in a C4-2 tumor bearing BALB/c nu/nu mouse model. All 68Ga-labeled ligands were stable in human serum over 2 h; 177Lu-CA030 was stable over 72 h. The PSMA ligands revealed inhibition potencies [Ki] (equilibrium inhibition constants) between 4.8 and 33.8 nM. The percentage of internalization of the injected activity/106 cells of 68Ga-CA028, 68Ga-CA029 and 68Ga-CA030 was 41.2 ± 2.7, 44.3 ± 3.9 and 53.8 ± 5.4 respectively; for the comparator 68Ga-PSMA-617 15.5 ± 3.1 was determined. Small animal PET-imaging of the compounds showed a high tumor-to-background contrast. Organ distribution studies revealed high specific uptake in the tumor, i.e. approximately 34.4 ± 9.8 percentage of injected dose per gram (%ID/g) at 1 h post injection for 68Ga-CA028. At 1 h p.i. 68Ga-CA028 and 68Ga-CA030 demonstrated lower kidney uptake than 68Ga-PSMA-617, but at later time-points kidney time-activity-curves converge. In line with the preclinical data, first diagnostic PET imaging using 68Ga-CA028 and 68Ga-CA030 revealed high-contrast detection of bone and lymph node lesions in patients with metastatic prostate cancer. The novel PSMA ligands, in particular CA028 and CA030, are promising agents for targeting PSMA-positive tumor lesions as shown in the preclinical evaluation and in a first patient, respectively. Thus, clinical translation of 68Ga-CA028 and 68Ga/177Lu-CA030 for diagnostics and endoradiotherapy of prostate cancer in larger cohorts of patients is warranted.